2010
DOI: 10.1007/s10126-010-9300-4
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Community Dynamics in the Marine Sponge Rhopaloeides odorabile Under In Situ and Ex Situ Cultivation

Abstract: Cultivation of sponges is being explored to supply biomaterial for the pharmaceutical and cosmetics industries. This study assesses the impact of various cultivation methods on the microbial community within the sponge Rhopaloeides odorabile during: (1) in situ cultivation under natural environmental conditions, (2) ex situ cultivation in small flow-through aquaria and (3) ex situ cultivation in large mesocosm systems. Principal components analysis of denaturing gradient gel electrophoresis profiles indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 33 publications
2
43
0
Order By: Relevance
“…This is consistent with the previous study of bacterial community by Kim and colleagues (2008), where they found WS3 to be the most abundant candidate phylum in the tidal flat sediment geographically close to our sampling site. The candidate phylum WS3 has been reported to be present in a variety of niches such as mud volcano (Kormas et al, 2008), marine sponge (Webster et al, 2010), sulfur-rich spring (Elshahed et al, 2007), anaerobic sludge digester (Chouari et al, 2005), and rice roots (Derakshani et al, 2001). With pyrosequencing, the percentage of candidate divisions was shown to decrease with depth from 1.7% at the surface to 1.2% at 5 m depth, and to 1.2% at 20 m depth (Fig.…”
Section: (A) (B)mentioning
confidence: 87%
“…This is consistent with the previous study of bacterial community by Kim and colleagues (2008), where they found WS3 to be the most abundant candidate phylum in the tidal flat sediment geographically close to our sampling site. The candidate phylum WS3 has been reported to be present in a variety of niches such as mud volcano (Kormas et al, 2008), marine sponge (Webster et al, 2010), sulfur-rich spring (Elshahed et al, 2007), anaerobic sludge digester (Chouari et al, 2005), and rice roots (Derakshani et al, 2001). With pyrosequencing, the percentage of candidate divisions was shown to decrease with depth from 1.7% at the surface to 1.2% at 5 m depth, and to 1.2% at 20 m depth (Fig.…”
Section: (A) (B)mentioning
confidence: 87%
“…Marine sponges are ecologically important components of the benthic community due to their wide diversity and high biomass (Ilan et al, 2004; de Goeij et al, 2013). In addition, they play a key functional role linking benthic and pelagic ecosystems, as they efficiently remove particulate organic carbon from the seawater (Díaz and Rützler, 2001; Ilan et al, 2004; Webster et al, 2011). Indeed, these sessile invertebrates are able to filter considerable amounts of seawater; a 1 kg sponge can filter up to 24000 L of water per day (Vogel, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have reported higher levels of variability across seasons (74) and when repeatedly sampling the same individuals over time (3), indicating some degree of symbiont fluctuation over time and individual variation among hosts. The prospect of sponge aquaculture for the production of bioactive metabolites has prompted investigations of host-symbiont stability under ex situ aquarium conditions, revealing high symbiont stability over short-term time scales (11 days to 12 weeks [23,67]), while longer-term maintenance (6 months to 2 years) can result in substantial shifts in symbiont composition (39,40,67). Additional studies of temporal variation in sponge-associated bacteria under natural conditions will aid future aquaculture efforts by determining natural variation in the sponge microbiota and its consequences for host-symbiont dynamics.…”
mentioning
confidence: 99%